The role of the genetic factor of lactate transport in endurance sports - Rafia Fathi; Abdul Al Majidi; Khamael Nhab; Rehab Ramadhan; Ratko Pavlović (Здоров’я, спорт, реабілітація, 2025)
Background and purpose